Mechanofluorochromic properties of aggregation-induced emission-active tetraphenylethene-containing cruciform luminophores. (September 2018) - Wang, Yonghui; Xu, Defang; Gao, Huaizhi; Wang, Ying; Liu, Xingliang; Han, Aixia; Zhang, Chao; Zang, Ling
Abstract: Two twisted donor–acceptor cruciform luminophores (DHCS-TPE andDMCS-TPE ) that were composed of two π-conjugated segments connected via a central benzene core have been prepared. Such cruciforms showed unique intramolecular charge transfer (ICT) emission, obvious aggregation-induced emission (AIE) properties (αAIE  = 19 and 20, respectively) and high solid state efficiency (0.913 and 0.424, respectively). Especially, the two compounds exhibited substituent-dependent mechanofluorochromic (MFC) behavior. The as-prepared powders of the more twistedDMCS-TPE could emit strong blue-green light centered at 474 nm, and the fluorescence color changed into yellowish green (531 nm) after grinding, a red shift of 57 nm was observed. Such mechanochromism was reversible upon the treatment of grinding and fuming with DCM. The high contrast MFC behavior ofDMCS-TPE originated from the planarization of the molecular conformation and subsequent planar intramolecular charge transfer (PICT) under external force. By sharp contrast, the less twistedDHCS-TPE exhibited no MFC behavior. The reason is that the less twisted molecular conformation ofDHCS-TPE generates strong intermolecular forces and close packing. Thus compared toDMCS-TPE, the crystalline solid powders ofDHCS-TPE possess higher lattice energy and better structural stability. The grinding of the crystalline solid powders ofDHCS-TPE cannot lead to amorphization and mechanochromic luminescence. Graphical abstract: Highlights: Two twisted donor–acceptor π-conjugated cruciform luminophores showed unique ICT properties. They exhibited evident aggregation-induced emission characteristics and high solid state efficiency. Their different mechanofluorochromic behavior was controlled by the molecular conformation induced by substituents.